Formulasi dan Evaluasi Foot Crack Cream Kombinasi Hyaluronic Acid dan Ekstrak Kunyit (Curcuma longa): Pendekatan Peningkatan Kelembaban - Siampa, Jainer Pasca; Datu, Olvie Syenni; Lebang, Julianri Sari (Sam Ratulangi University, 2025)
Daily routine activities exposed to sunlight, air pollution, changes in air humidity and ambient temperature, the use of cleansing soap, and even activities using air conditioning can cause a decrease in skin moisture. This study aimed to formulate a foot crack cream preparation using a combination of hyaluronic acid and turmeric extract that met the requirements for physical characterization of the preparation. The formulas to be made were 3 formulas with varying concentrations of turmeric extract combined with hyaluronic acid at a constant concentration. The obtained formulas were then evaluated physically including organoleptic observations, pH measurements, spreadability testing, adhesion testing and emulsion type testing. The results obtained a semi-solid foot crack cream formula, light canary to mustard in color; pH 6; spreadability value of 6.1 cm- 6.5 cm; adhesion of more than 1 second and had an oil-in-water emulsion type. From the results of this study, could be concluded that the obtained foot crack cream preparation formula using a combination of hyaluronic acid and turmeric extract met the requirements for physical characterization of the preparation.